2012
DOI: 10.5424/sjar/2013113-3808
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid composition of muscle and internal fat depots of organic and conventional Payoya goat kids

Abstract: Interest in the preservation of autochthonous breeds such as the Payoya goat (dairy breed), raised using extensive or semi-extensive grazing, has also recently increased among Spanish farmers. A study of the possibilities of transformation to organic production needs to analyze the quality of their products, specially the suckled kids. The objective of this study was to evaluate the fatty acid (FA) composition of Payoya goat kids under organic and conventional grazing–based management system. Forty-eight goat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
5
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 37 publications
4
5
0
3
Order By: Relevance
“…Nevertheless, World Health Organization has changed its recommendation from 5-10 ( WHO, 1995) to conclude recently that there is no rational for a specific recommendation for n-6 to n-3 ratio, if intakes of n-6 and n-3 fatty acids lie within the recommendation established (WHO, 2010). In the present study, the n-6 PUFA:n-3 PUFA ratio was lower than those reported in other studies on goats (Todaro et al, 2004;Sanz Sampelayo et al, 2006;Nudda et al, 2008), but was comparable to those reported for the fat depots and muscles of grazing goats (Bas et al, 2005;Horcada et al, 2012;De la Vega et al, 2013). Also, organic kid meat and specially the fat depots displayed higher percentages of several n-3 FA than conventionally reared meat, in agreement with a study of goats under similar grazing based system (De la , which might be a consequence of high pasture intake by organically managed dams due to reduced feedstuff supplementation.…”
Section: Fatty Acid Composition Of Muscle and Fat Depots Of Blanca Ansupporting
confidence: 80%
See 4 more Smart Citations
“…Nevertheless, World Health Organization has changed its recommendation from 5-10 ( WHO, 1995) to conclude recently that there is no rational for a specific recommendation for n-6 to n-3 ratio, if intakes of n-6 and n-3 fatty acids lie within the recommendation established (WHO, 2010). In the present study, the n-6 PUFA:n-3 PUFA ratio was lower than those reported in other studies on goats (Todaro et al, 2004;Sanz Sampelayo et al, 2006;Nudda et al, 2008), but was comparable to those reported for the fat depots and muscles of grazing goats (Bas et al, 2005;Horcada et al, 2012;De la Vega et al, 2013). Also, organic kid meat and specially the fat depots displayed higher percentages of several n-3 FA than conventionally reared meat, in agreement with a study of goats under similar grazing based system (De la , which might be a consequence of high pasture intake by organically managed dams due to reduced feedstuff supplementation.…”
Section: Fatty Acid Composition Of Muscle and Fat Depots Of Blanca Ansupporting
confidence: 80%
“…Also and except for fat depots, in this study there were no significant differences between the atherogenicity index in goat kid from organic or conventional managed dams. In addition, the atherogenicity index values for both groups were similar to those observed by De la Vega et al (2013), but lower than those reported in milk of sheep fed Mediterranean forages (Addis et al, 2005). The low fat content and FA prof ile (especially the PUFA content and the n-6:n-3 PUFA ratio) of meat from kids reared in both production systems indicates the beneficial characteristics of this meat with respect to human health.…”
Section: Fatty Acid Composition Of Muscle and Fat Depots Of Blanca Ansupporting
confidence: 69%
See 3 more Smart Citations